The effect of alcohol and red wine consumption on clinical and MRI outcomes in multiple sclerosis - Diaz-Cruz, Camilo; Chua, Alicia S.; Malik, Muhammad Taimur; Kaplan, Tamara; Glanz, Bonnie I.; Egorova, Svetlana; Guttmann, Charles R.G.; Bakshi, Rohit; Weiner, Howard L.; Healy, Brian C.; Chitnis, Tanuja (Multiple sclerosis and related disorders, 2017)
Alcohol and in particular red wine have both immunomodulatory and neuroprotective properties, and may exert an effect on the disease course of multiple sclerosis (MS). To assess the association between alcohol and red wine consumption and MS course. MS patients enrolled in the Comprehensive Longitudinal Investigation of Multiple Sclerosis at the Brigham and Women's Hospital (CLIMB) who completed a self-administered questionnaire about their past year drinking habits at a single time point were included in the study. Alcohol and red wine consumption were measured as servings/week. The primary outcome was the Expanded Disability Status Scale (EDSS) at the time of the questionnaire. Secondary clinical outcomes were the Multiple Sclerosis Severity Score (MSSS) and number of relapses in the year before the questionnaire. Secondary MRI outcomes included brain parenchymal fraction and T2 hyperintense lesion volume (T2LV). Appropriate regression models were used to test the association of alcohol and red wine intake on clinical and MRI outcomes. All analyses were controlled for sex, age, body mass index, disease phenotype (relapsing vs. progressive), the proportion of time on disease modifying therapy during the previous year, smoking exposure, and disease duration. In the models for the MRI outcomes, analyses were also adjusted for acquisition protocol. 923 patients (74% females, mean age 47 ± 11 years, mean disease duration 14 ± 9 years) were included in the analysis. Compared to abstainers, patients drinking more than 4 drinks per week had a higher likelihood of a lower EDSS score (OR, 0.41; p = 0.0001) and lower MSSS (mean difference, − 1.753; p = 0.002) at the time of the questionnaire. Similarly, patients drinking more than 3 glasses of red wine per week had greater odds of a lower EDSS (OR, 0.49; p = 0.0005) and lower MSSS (mean difference, − 0.705; p = 0.0007) compared to nondrinkers. However, a faster increase in T2LV was observed in patients consuming 1–3 glasses of red wine per week compared to nondrinkers. Higher total alcohol and red wine intake were associated with a lower cross-sectional level of neurologic disability in MS patients but increased T2LV accumulation. Further studies should explore a potential cause-effect neuroprotective relationship, as well as the underlying biological mechanisms. •Moderate alcohol consumption was associated with lower EDSS score and MSSS.•Drinking > 3 glasses of red wine/week was associated with lower EDSS score and MSSS.•Subjects drinking 1–3 glasses of red wine/week had an increase in MRI lesion volume accumulation.